Abnormal lipopolysaccharide binding protein as marker of gastrointestinal inflammation in Parkinson disease - Pal, Gian; Shaikh, Maliha; Forsyth, Christopher; Ouyang, Bichun; Keshavarzian, Ali; Shannon, Kathleen (Frontiers in Neuroscience, 2015)
Objective: To evaluate whether lipopolysaccharide binding protein (LBP) can be used to distinguish PD subjects from control subjects and to assess whether LBP levels correlate with PD disease severity. Methods: We measured plasma LBP (ng/ml) using an ELISA kit in 94 PD subjects of various stages and 97 control subjects. Disease severity was assessed using the UPDRS and Hoehn and Yahr staging. The LBP level between the PD and control groups was compared using analysis of covariance. Spearman correlation was used to explore the relationship between LBP level and disease severity. Results: The mean LBP level in PD subjects (n=94) was significantly different from control subjects (n=95, p=0.018). In PD subjects, we did not find a correlation between mean LBP level and disease severity. Conclusions: Our data suggests that LBP is one GI biomarker related to LPS induced neurotoxicity. However, there was significant variability in LBP levels within the PD and control groups, limiting its utility as a stand-alone biomarker. This study supports the role of LPS induced neurotoxicity in PD and further exploration of this pathway may be useful in developing sensitive and specific biomarkers for PD.